Outcome of surgical embolectomy in patients with massive pulmonary embolism with and without cardiopulmonary resuscitation - Hajizadeh, Reza; Ghaffari, Samad; Habibzadeh, Afshin; Safaei, Naser; Mohammadi, Kamran; Ranjbar, Abdolmohammad; Ghodratizadeh, Sahar (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Introduction : Pulmonary embolism is a challenging critical cardiovascular disease with high morbidity and mortality. Surgical embolectomy has favorable results in patients with massive pulmonary embolism. Aim : To study the outcome of embolectomy in patients with massive pulmonary embolism. Material and methods : In this single-center, retrospective study, 36 patients including 14 male and 22 female patients with a mean age of 50.80 ±18.89 years with acute pulmonary embolism who underwent surgical pulmonary embolectomy from January 2011 to January 2016 were included. The medical records of all patients were reviewed for demographic and preoperative data and postoperative outcomes. Results : Common risk factors for acute PE were major surgery within 3 months and deep vein thrombosis. The most common presenting symptoms of patients were dyspnea, followed by chest pain and syncope. Mean duration of hospitalization was 14.76 ±8.69 days and mean operation duration was 4.47 ±1.54 h. Mean time from admission to embolectomy was 6.58 ±1.13 h. Ten (27.8%) patients died during the operation including 3 cases with cardiopulmonary resuscitation prior to surgery and 2 cases with severe cardiogenic shock. Patients who survived were followed for 6 months. The mortality rate during follow-up was 15.4%; all 4 patients died during follow-up period due to metastatic cancer. No pulmonary embolism recurrance were seen. Conclusions : Although surgical embolectomy mostly was done for high risk patients, it had good in-hospital and excellent mid-term outcomes.